The Difference Between Saying and Doing: Comparing Subjective and Objective Measures of Effort Among Fifth Graders - Paula Apascaritei; Simona Demel; Jonas Radl (American Behavioral Scientist, 2021)
The first goal of this study is to examine the capacity of prominent survey-based effort proxies to predict real effort provision in children. Do children who "talk the talk" of hard work also "walk the walk" and make costly effort investments? The second goal is to assess how objective and subjective effort measures are related under two conditions: intrinsic (nonincentivized) motivation and extrinsic (incentivized) motivation. We measure objective "real" effort using three tasks and subjective self-reported effort using four psychological characteristics (conscientiousness, need for cognition, locus of control and delay of gratification) to understand to what extent material incentives affect the cognitive effort of children with different self-reported personalities. Data stem from real-effort experiments carried out with 420 fifth grade students from primary schools in Madrid, Spain. We find that some of the subjective and objective effort measures are positively correlated. Yet the power of personality to predict real effort is only moderate, but greater and more so in the extrinsic than the intrinsic motivation condition. In particular, need for cognition and conscientiousness are the most relevant correlates of objective effort. Overall, we find there is a big difference between saying and doing when it comes to exerting effort, and this difference is even larger when there are no direct material incentives in place to reward effort provision.
doi:10.25384/SAGE.14161797.v1
Keywords: 330; cognitive effort; personality; incentives; laboratory experiment